Was Christ crucified? debate in Canada - Deedat, Ahmed (Dubai : Islamic Propagation Center International [production company] ; Kuala Lumpur : SABA Islamic Media [distributor])
This is the 1st debate in Canada between Sheikh Ahmed Deedat with Bishop General Wakefield (An Evangelist Of Canada)
Speaker: Ahmed Deedat
Keywords: Bible -- Criticism, interpretation, etc; Jesus Christ -- Islamic interpretations